Spanish museums on Facebook: analysis of their communication as social museums - Mas Iglesias, J. M. (Revista de Comunicación, 2018)
In recent years, the irruption of digital technologies forces museums not only to try to take advantage of these new possibilities but also to seek to optimize them to strengthen the achievement of a more social, participatory and collaborative museum, in line with what other cultural institutions are doing as well. In this context, social networks in general –and Facebook in particular- can offer many opportunities. The aim of this paper is to analyze the communication of Spanish museums in this service in order to assess the extent to which they are using it in this sense. To do so, we have carried out a content analysis of the messages posted during 6 months by the 10 most followed Spanish museums on Facebook. Results confirm that its promotional use prevails, both in quantity and variety, over other modalities more aimed at creating community, as might be expected from a social museum.